PENERAPAN KURIKULUM BERTARAF INTERNASIONAL DI MA AMANATUL UMMAH PACET - Chusnul Chotimah; Khoirun Nisa' (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2019)
Excellence in International Standard Madrasas in the field of education has competitiveness in international forums and refers to the education standards of one of the other developed countries. The aim of this study is to describe, study and analyze the preparation of educational programs in providing quality learning that is appropriate to the needs and carried out according to the learning program and students to be able to evaluate learning outcomes in accordance with the learning program that has been designed by the teacher. The Amanatul Ummah MBI is one of the madrasas that has its own uniqueness in achieving outstanding achievements and easy students in continuing to study at domestic universities and overseas universities in the scholarship guarantees, on this basis the researchers decided to conduct research related to the curriculum. The research method used in this study is a qualitative research method. Judging from the type, this research is a case study, because this research is conducted intensively, in detail and fundamentally about an institution, where researchers take the case of developing an international curriculum. Talking about the international standard curriculum in public schools is certainly not enough with one strategy, there must be continued and harmonized relations between religious teachers and general teachers and the local community.